2022
DOI: 10.3390/ijerph19106113
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Telemedicine during the COVID-19 Pandemic—A Systematic Review

Abstract: Telemedicine is a convenient tool for providing medical care remotely. It is routinely offered as an alternative to face-to-face consultations in healthcare settings all over the world. Due to the COVID-19 pandemic and increased use of telemedicine in everyday clinical practice, the effectiveness of this modality and patient satisfaction with telemedicine is a subject of growing concern. PubMed and Google Scholar databases were searched. Papers published between January 2020 and August 2021 which met inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…Conversely, patient motivation, engagement, and empowerment were considered the main facilitators, enabling patients to use telemedicine easily [78,[83][84][85]. Access to a helpful caregiver, insight into the home environment, and adoption of digital culture might reduce resistance, as the pandemic has shown [86]. Patients who trusted technology and were satisfied with web-based consultations showed no resistance to telemedicine, felt safe and empowered to discuss personal issues, and had experiences similar to those with face-to-face consultations.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Conversely, patient motivation, engagement, and empowerment were considered the main facilitators, enabling patients to use telemedicine easily [78,[83][84][85]. Access to a helpful caregiver, insight into the home environment, and adoption of digital culture might reduce resistance, as the pandemic has shown [86]. Patients who trusted technology and were satisfied with web-based consultations showed no resistance to telemedicine, felt safe and empowered to discuss personal issues, and had experiences similar to those with face-to-face consultations.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Finally, we report a high satisfaction rate about follow-up during COVID-19 in Ph-MPN patients, which we can consider a success taking into account the Public Health difficulties and overload during this period. In this regard, a recent systematic review from a Polish group confirmed a high level of satisfaction with telehealth in each study across every medical specialty [ 18 ]. 82.3% of patients in this study endorsed using telemedicine again, although these opinions were collected during the pandemic, so we cannot assume patient attitudes will not change afterwards.…”
Section: Discussionmentioning
confidence: 97%
“…The rationale for the survey was to capture patients’ attitudes, opinions, and preferences, as well as suggestions to improve follow-up in the future. Compared to similar studies including patients’ surveys, we present the greatest response rate to our knowledge, which makes the data more valuable [ 18 ][ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, younger age and female gender were associated with lower patient satisfaction [58]. A high level of satisfaction with telehealth was observed in studies across medical specialties, but emergency medicine was not included in any of the research [59]. Lack of opinions of emergency department patients may result from the difficulties in measuring patient satisfaction in a situation of an imminent threat to one's life.…”
Section: Limitations Of Telehealth Usementioning
confidence: 99%